I Am/Was the Walrus - Beller-McKenna, Daniel (Current Musicology, 2002)
For most of his adult life, John Lennon fought to define himself against his public identity as "Beatle-:John." That image, crafted by the Beatles' manager Brian Epstein and the pop music industry became a burden to all four of the Beatles during the group's seven years of international star-dom. In place of the rough leather-clad rock and roll band that played rambling one hour sets in the Hamburg Kaiserkeller and the Liverpool Cavern Club during 1960-61, Epstein forged a more commercially viable group of four well (and uniformly) dressed young men whose stage act was reduced to twenty minute carefully scripted sets.